ChemInform Abstract: Computing Organic Stereoselectivity — From Concepts to Quantitative Calculations and Predictions. Issue 51 (5th December 2016) - Peng, Qian; Duarte, Fernanda; Paton, Robert S.
Abstract: Review: 49 refs.